Mekanisme Pengungkapan Emisi Karbon dan Reaksi Investor - Kelvin, Chen; Pasoloran, Oktavianus; Randa, Fransiskus (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019)DO - 10.24843/JIAB.2019.v14.i02.p02, 2019)
This research aims to investigate the role of carbon emission disclosure as a mechanism to improve investors' reaction to abnormal stock returns mediated by cost of equity. The samples used in this study were non-financial companies listed on the Indonesia Stock Exchange from 2013 to 2017. There were 122 companies with 610 observations. The samples were selected using the purposive sampling method. By using the path analysis method, the results show that carbon emission disclosure has a negative relationship with the cost of equity, carbon emission disclosure has a positive relationship with abnormal stock return, while the cost of equity has a negative and significant relationship with abnormal stock return. Additionally, the results obtained using the Sobel test show that the cost of equity plays a role in mediating the relationship between carbon emission disclosure and abnormal stock returns. Keywords: carbon emission disclosure; cost of equity; abnormal stock returns